Steroid Hormone Receptors: Links With Cell Cycle Machinery and Breast Cancer Progression - Saha, Suryendu; Dey, Samya; Nath, Somsubhra (Frontiers in Oncology, 2021)
Progression of cells through cell cycle consists of a series of events orchestrated in a regulated fashion. Such processes are influenced by cell cycle regulated expression of various proteins where multiple families of transcription factors take integral parts. Among these, the steroid hormone receptors (SHRs) represent a connection between the external hormone milieu and genes that control cellular proliferation. Therefore, understanding the molecular connection between the transcriptional role of steroid hormone receptors and cell cycle deserves importance in dissecting cellular proliferation in normal as well as malignant conditions. Deregulation of cell cycle promotes malignancies of various origins, including breast cancer. Indeed, SHR members play crucial role in breast cancer progression as well as management. This review focuses on SHR-driven cell cycle regulation and moving forward, attempts to discuss the role of SHR-driven crosstalk between cell cycle anomalies and breast cancer.